Risk factor analysis of type 2 diabetes mellitus in rural areas: A systematic review - Yoki Arum Sari; Najmah Najmah; Rico Januar Sitorus (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Type 2 diabetes mellitus (DM) prevalence continues to increase in rural areas, which is of particular concern due to limited access to health services in these areas. Purpose: To identify various risk factors for the incidence of type 2 DM in rural areas for the development of effective prevention programs. Method: Systematic review is based on PRISMA guidelines. Searches were conducted in Scopus, Science Direct, and SINTA for 2020-2025 articles. Data were extracted and analyzed narratively based on the type of risk factors that were found. Results: Out of 856 articles, 20 studies met the inclusion criteria. Dominant risk factors identified included obesity (OR range 2.15-3.05), family history of DM (OR range 2.13-4.46), and low physical activity (OR range 2.94-7.43). Additional risk factors include hypertension, unhealthy food environment, and unhealthy diet. Several studies reported an increased incidence of type 2 DM in younger populations in rural areas. Conclusion: Obesity, family history of DM, and low physical activity are the dominant risk factors for type 2 DM in rural areas. These factors are important targets for health policy interventions, especially given the increasing incidence in younger populations in rural areas.